COMMUNICATION INTER-RELIGIOUS IN THE TOLERANCE LIFE OF JAMIKA SOCIETY - BANDUNG CITY - Sariwaty, Yulia; Fitriawati, Dini; Retnasary, Maya; Samiaji (Jurnal Komunikasi dan Bisnis, 2022)
The research was conducted to find out how inter-religious harmony was built by the Jamika, Bandung society to create a good life of tolerance in the midst of social life. The research method used is a qualitative method, through a descriptive analysis approach. Data collection techniques were obtained through interviews and observations. The results of research show that communication is the key to the success of inter-religious harmony in building a life of tolerance in the midst of the diversity of Jamika residents of Bandung. Community leaders, youth leaders and different religious leaders have created a forum for friendship in strengthening tolerance that has been strong for generations. A good tolerance life in the Jamika community has received positive appreciation from the Bandung city government and the West Java provincial government, this is proven by the making of Jamika village, especially RW 04 society or better known as gang Luna gang Luna as a tolerance village to become a pilot village for residents in other areas.